Aspirin for Stroke Prevention in Elderly Patients With Vascular Risk Factors: Japanese Primary Prevention Project. Issue 6 (June 2016) - Uchiyama, Shinichiro; Ishizuka, Naoki; Shimada, Kazuyuki; Teramoto, Tamio; Yamazaki, Tsutomu; Oikawa, Shinichi; Sugawara, Masahiro; Ando, Katsuyuki; Murata, Mitsuru; Yokoyama, Kenji; Minematsu, Kazuo; Matsumoto, Masayasu; et al.
Abstract : Background and Purpose—: The effect of aspirin in primary prevention of stroke is controversial among clinical trials conducted in Western countries, and no data are available for Asian populations with a high risk of intracranial hemorrhage. The objective of this study was to evaluate the effect of aspirin on the risk of stroke and intracranial hemorrhage in the Japanese Primary Prevention Project (JPPP). Methods—: A total of 14 464 patients (age, 60–85 years) with hypertension, dyslipidemia, and diabetes mellitus participated and were randomized into 2 treatment groups: 100 mg of aspirin or no aspirin. The median follow-up period was 5.02 years. Results—: The cumulative rate of fatal or nonfatal stroke was similar for the aspirin (2.068%; 95% confidence interval [CI], 1.750–2.443) and no aspirin (2.299%; 95% CI, 1.963–2.692) groups at 5 years; the estimated hazard ratio was 0.927 (95% CI, 0.741–1.160; P =0.509). Aspirin nonsignificantly reduced the risk of ischemic stroke or transient ischemic attack (hazard ratio, 0.783; 95% CI, 0.606–1.012; P =0.061) and nonsignificantly increased the risk of intracranial hemorrhage (hazard ratio, 1.463; 95% CI; 0.956–2.237; P =0.078). A Cox regression adjusted by the risk factors for all stroke, which were age >70 years, smoking, and diabetes mellitus, supported the above result. Conclusions—: Aspirin did not show any net benefit for the primary prevention of stroke in elderly Japanese patients with risk factors for stroke, whereas age >70 years, smoking, and diabetes mellitus were risk factors for stroke regardless of aspirin treatment. Clinical Trial Registration—: URL: http://www.clinicaltrials.gov. Unique identifier: NCT00225849. Abstract : Supplemental Digital Content is available in the text.